Angioplasty of femoral-popliteal arteries with drug-coated balloons: 5-year follow-up of the THUNDER trial - Tepe, Gunnar; Schnorr, Beatrix; Albrecht, Thomas; Brechtel, Klaus; Claussen, Claus D; Scheller, Bruno; Speck, Ulrich; Zeller, Thomas (JACC. Cardiovascular interventions, 2015)
The purpose of this study was to evaluate the 5-year follow-up (FU) data of the THUNDER (Local Taxan With Short Time Contact for Reduction of Restenosis in Distal Arteries). The THUNDER trial was the first study to investigate the treatment of femoropopliteal arteries with a paclitaxel-coated balloon (PCB). In 154 patients, femoropopliteal arteries were treated with PCB, with angioplasty with paclitaxel in contrast medium, or no paclitaxel (control). The primary endpoint was 6-month late lumen loss (LLL). Secondary endpoints included freedom from target lesion revascularization (TLR), binary restenosis rate, and amputation. The 5-year FU compares outcomes in patients treated with PCB and control subjects. Additionally, LLL at 6 months and TLR up to 5-year FU were analyzed in terms of sex and lesion length. Over the 5-year period, the cumulative number of patients with TLR remained significantly lower in the PCB group (21%) than in the control group (56%, p = 0.0005). In the small group of patients with angiographic and duplex sonographic follow-up, PCB was associated with a lower rate of binary restenosis (17% vs. 54%; p = 0.04). No signs of aneurysm formation or constrictive fibrosis were detected. Whereas LLL at 6-month FU did not differ between men and women in the PCB group, the TLR rate was lower in men than in women at 5-year FU. A benefit of PCB treatment in terms of LLL and TLR was seen independent of lesion length. The reduced TLR rate following PCB treatment was maintained over the 5-year FU period. No signs of drug-related local vessel abnormalities were detected. (Thunder Trial-Local Taxan With Short Time Contact for Reduction of Restenosis in Distal Arteries [THUNDER]; NCT00156624).